An active feedback recovery technique from disruption events induced by m = 2, n = 1 tearing modes in ohmically heated tokamak plasmas. (April 2015) - Zanca, P.; Paccagnella, R.; Finotti, C.; Fassina, A.; Manduchi, G.; Cavazzana, R.; Franz, P.; Piron, C.; Piron, L.
Abstract We present experimental results of magnetic feedback control on the m = 2, n = 1 tearing mode in RFX-mod operated as a circular ohmically heated tokamak. The feedback suppression of the non-resonant m = 2, n = 1 resistive wall mode (RWM) in q(a) < 2 plasmas is a well-established result of RFX-mod. The control of the tearing counterpart, which develops in q(a) > 2 equilibrium, is instead a more difficult issue. In fact, the disruption induced by a growing amplitude m = 2, n = 1 tearing mode can be prevented by feedback only when the resonant surface q = 2 is close to the plasma edge, namely 2 < q(a) < 2.5, and the electron density does not exceed approximately half of the Greenwald limit. The RFX-mod data show very clearly that a large amplitude m = 2, n = 1 tearing mode significantly limits the operative region of plasma parameters even in the presence of an efficient magnetic feedback. A combined technique of tearing mode and q(a) control has been therefore developed to recover the discharge from the most critical conditions: the potentially disruptive tearing mode is converted into the relatively benign RWM by suddenly decreasing q(a) below 2. The experiments successfully demonstrate the concept. The q(a) control has been performed through the plasma current, given the capability of the toroidal loop-voltage power supply of RFX-mod. We also propose a path for decreasing q(a) by acting on the plasma shape, which could be applied to medium size elongated tokamaks.